2018
DOI: 10.1371/journal.pone.0192571
|View full text |Cite
|
Sign up to set email alerts
|

Income, occupation and education: Are they related to smoking behaviors in China?

Abstract: BackgroundThe association between socioeconomic status (SES) and smoking behaviors may differ across countries. This study aimed to estimate the association between socioeconomic status (income, occupation and education) and multiple measures of smoking behaviors among the Chinese elderly population.MethodsUsing data from the China Health and Retirement Longitudinal Study in 2013, we examined the relationship between socioeconomic status and smoking behaviors through multivariate regression analysis. Sample se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
85
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(110 citation statements)
references
References 56 publications
14
85
1
10
Order By: Relevance
“…Therefore, it is thought that education has a profound effect on smoking initiation on the younger population, while occupation can affect smoking cessation of the middle-age and older population. 19,36 With respect to the association between education and smoking, less educated persons are less likely to have the opportunity to acquire knowledge about smoking and its health effects than those having higher education, leading to a higher prevalence of current smoking in those individuals. 37 Additionally, living in a society that demands high academic qualifications seems to be one reason for increased difference in smoking prevalence between university-educated persons and junior high school graduates among young people.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, it is thought that education has a profound effect on smoking initiation on the younger population, while occupation can affect smoking cessation of the middle-age and older population. 19,36 With respect to the association between education and smoking, less educated persons are less likely to have the opportunity to acquire knowledge about smoking and its health effects than those having higher education, leading to a higher prevalence of current smoking in those individuals. 37 Additionally, living in a society that demands high academic qualifications seems to be one reason for increased difference in smoking prevalence between university-educated persons and junior high school graduates among young people.…”
Section: Discussionmentioning
confidence: 99%
“…41 For the association between occupation and smoking, many studies have reported a significant association between lower level occupations and a higher percentage of current smokers. 13,[19][20][21][22][23][24] It is well known that people with lower level occupations have more difficulties in successfully quitting smoking than those with higher level occupations because they are less likely to receive treatment and support to quit. 42 Another reason for a high rate of smoking in manual workers may be their hard physical tasks or a common practice of smoking at their workplace.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations